JAKARTA COMPOSITE INDEX (JCI) MOVEMENT : CASE STUDY BASED ON SHORT TERM DATA OF THE FED'S INTEREST RATE, BI RATE AND INFLATION - ADITYA ACHMAD RAKIM; MAKMURI AHDI; DIENI NURUL ALIYYA (Fakultas Ekonomi dan Bisnis Islam, 2022)
Increase in the Fed's interest rate will caused a large capital outflow that affected the capital market and investment in a country. Bank Indonesia interest rate (BI Rate) raise will trigger an increase in the inflation rate, raise in inflation will also have an impact on the amount of money revolving in the market. This study analyzed Jakarta Composite Index (JCI) movement base on the Fed's interest rate, BI Rate and inflation. The population used in this research is historical data of the Jakarta Composite Index (JCI) for the 2013-2017 period. The results of the JCI index movement data two weeks after the announcement of the Fed's rate raise indicated that the Fed's interest rates were proven. The results of the test of the effect of the BI Rate on the index movement indicate that an increase in the BI Rate of market participants will respond positively. While an increase in the inflation rate will cause a negative response by market participants due to the decline in the level of corporate profits